2016
DOI: 10.6017/ijahe.v2i1.9260
|View full text |Cite
|
Sign up to set email alerts
|

Shifting from Government Bursaries to a Loan Scheme in Higher Education: Exploring the Zambian Experience in Student Financial Aid

Abstract: One of the current critical issues in higher education in Africa and globally is about making student loans available in a sustainable and cost-effective manner. The argument is more complicated for Africa because of the complexities associated with loan schemes and the general austerity that African countries find themselves in. This article presents a case study and conceptualizes the scenario of shifting government bursaries to a student loan scheme in Zambia's higher education sector. Based on student view… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 17 publications
0
16
0
Order By: Relevance
“…The different financing and testing mechanisms are therefore put in place to promote access to tertiary education by students with sound intellectual capacity but with no financial capacity to pay for their education. For example, countries such as Kenya, Ghana, South Africa, Tanzania and Uganda, have introduced student bursaries and loans as a means of promoting equitable access to tertiary education and government financial subsidies (Tekleselassie & Johnstone, 2004;Masaiti, Mwelwa & Mwale, 2016). However, to ensure that loans and bursary grants are given to deserving students from poor families and households so that they access tertiary education, many African governments are now coming up with context specific 'means testing mechanisms' to ensure that only genuine households with no capacity to support their children to access post-secondary education are given the financial support to access quality higher education in areas of primary importance for both personal and national development.…”
Section: Contextmentioning
confidence: 99%
“…The different financing and testing mechanisms are therefore put in place to promote access to tertiary education by students with sound intellectual capacity but with no financial capacity to pay for their education. For example, countries such as Kenya, Ghana, South Africa, Tanzania and Uganda, have introduced student bursaries and loans as a means of promoting equitable access to tertiary education and government financial subsidies (Tekleselassie & Johnstone, 2004;Masaiti, Mwelwa & Mwale, 2016). However, to ensure that loans and bursary grants are given to deserving students from poor families and households so that they access tertiary education, many African governments are now coming up with context specific 'means testing mechanisms' to ensure that only genuine households with no capacity to support their children to access post-secondary education are given the financial support to access quality higher education in areas of primary importance for both personal and national development.…”
Section: Contextmentioning
confidence: 99%
“…This was the case following the Zambian government's shift in the student financing policy of 2018. It was biased and inclined to offer more student bursaries and loans to those who were enrolled for STEM degrees in public universities (Masaiti, Mwelwa, & Mwale, 2015) in line with the national skills development agenda to achieve the vision 2030 (GRZ, 2006), as espoused by the human capital theory. It could be concluded that the Bachelor of Social Work graduates stood a better chance of being employed compared to those in the other three social science degrees.…”
Section: The Demand For Social Science Degree Programs In Selected Universitiesmentioning
confidence: 99%
“…While fees should be introduced, they should represent only a small proportion of the actual economic cost and should be accompanied by appropriate loan schemes or scholarships for the socially disadvantaged students. In this way, higher education will be available to all classes of youths in Africa (Masaiti, Mwelwa, and Mwale, 2016).…”
Section: Under Fundingmentioning
confidence: 99%